ANALISIS KINERJA KEUANGAN UMKM INDUSTRI KREATIF KOTA SURAKARTA - Mulyono, Muflik Malikun & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2018)
The creative industry sector in Surakarta has potential to compete in theera of the ASEAN Economic Community (AEC), to exploit the potential ofcreative Micro, Small and Medium Enterprises (MSMEs) in Surakarta shouldimprove productivity and company performance. This study aims to analyzeof financial performance of creative MSMEs in Surakarta with operating profitas a proxy of performance, as well as analyze of capital and sales.Hypothesis in this study (1) Capital influence on sales (2) Capital influence onMSMEs performance (3) Sales influence on MSMEs performance. This studytook a sample of 117 MSMEs entrepreneurs spread across 5 districts inSurakarta, with purposive sampling techniques. Hypothesis testing is done byusing multiple regression analysis. The conclusion of the hypothesis testresults (1) capital has positive and significant effect on sales, (2) capital hasnot significant effect on creative MSMEs (3) sales have positive andsignificant effect on the performance of creative MSMEs in Surakarta.Keywords: capital, sales, operating profit, performance of creative MSMEs